THE POSITIVE EFFECTS OF USING THE LEXICAL APPROACH FOR KIDS AT LEARNING ENGLISH - Revelo A., Javier Ricardo (Revista Huellas, 2019)
The lexical approach identifies lexis as the basis of language and focuses on the principle that language consists of grammaticalised lexis. In second language acquisition, over the past few years, this approach has generated great interest as an alternative to traditional grammar-based teaching methods. From a psycholinguistic point of view, the lexical approach consists of the capacity of understanding and producing lexical phrases as non-analyzed entities (chunks). The main objective to prove is to show the positive results of using the lexical approach for kids in a public school of Pasto, Colombia. Observations in behavior and exam results were taken as the main tool to see if the goal was accomplish. Fortunately, the goal was reached and leave important to consider.